ANALISIS HARGA SAHAM SEBELUM DAN SESUDAH PENGUMUMAN STOCK SPLIT(Studi pada Perusahaan yang Terdaftar di Bursa Efek Indonesia 2017-2020) - sari widati (Pusat P2M Politeknik Negeri Batam, 2023)
This study aims to analyze stock prices before and after the stock split. The sample of this research is Manufacturing Companies Listed on the Indonesia Stock Exchange in 2017-2020. The sampling technique used purposive sampling method. Based on the predetermined sampling criteria, a sample of 39 companies was obtained. This research is an event study in the field of capital markets. The results showed that there was no significant difference in stock prices for 10 days before and 10 days after the stock split